Overcoming Poverty through Social Entrepreneurship: A Conceptual Paper - Fakhrul Anwar, Zainol; Wan Norhayate, Wan Daud; Zulhamri, Abdullah (2014)
This paper aims to propose a conceptual framework to study the relationship between social entrepreneurship and organizational effectiveness. It also explains various theories of change that social entrepreneurs have pursued in overcoming urban poverty in the country. The study will utilize qualitative methods to collect primary data from social entrepreneurship organization in the main cities in Malaysia. The data from the interview will be evaluated to determine how organizational effectiveness can help social entrepreneurship to overcome urban poverty. Although no single social entrepreneurial venture had put a huge dent in poverty, there certainly have been many initiatives that have notable stories to tell about how they have helps poor people. Many researches are now needed to document which “social” returns on investments and to determine the strategies that lead to the best returns. The findings could benefit not only individual social entrepreneurs but also public, policy maker and firms by clarifying how much social entrepreneurship could be relied upon to help alleviate poverty compared to government and business initiatives. Therefore the findings of this research are expected to provide the view of how social entrepreneurship can give impact to urban poverty in the selected area through organizational effectiveness.